Perkaitan antara faktor iklim organisasi dengan motivasi kerja. Kajian kes ke atas Penolong Pendaftar. - Ezwandy, bin Mahidi. (Universiti Malaysia Sarawak (UNIMAS), 2002)
This study was conducted among the Assistants Registrar (formerly known as Managers) of University Malaysia Sarawak to detennine if their work motivation were related to organizational climate. Researcher used the questionnaire survey method and interview session. Researcher also applied t-Test, one -way ANOVA, Pearson correlation and Stepwise Regression analysis to explore relationship between these two variables. Major findings showed that most managers' demographic variables except ages factor prove na significant difference in the level of their work motivation. Correlation between organizational climate and work motivation are all positive. The result are also generally medium ranging between 0.339 -0.729. A Stepwise regression was performed for organizational climate factors. Responsibility emerging as significant predictors ofwork motivation.